Regulation of microglia related neuroinflammation contributes to the protective effect of Gelsevirine on ischemic stroke - Xing, Chunlei; Lv, Juan; Zhu, Zhihui; Cong, Wei; Bian, Huihui; Zhang, Chenxi; Gu, Ruxin; Chen, Dagui; Tan, Xiying; Su, Li; Zhang, Yu (Frontiers in Immunology, 2023)
Stroke, especially ischemic stroke, is an important cause of neurological morbidity and mortality worldwide. Growing evidence suggests that the immune system plays an intricate function in the pathophysiology of stroke. Gelsevirine (Gs), an alkaloid from Gelsemium elegans, has been proven to decrease inflammation and neuralgia in osteoarthritis previously, but its role in stroke is unknown. In this study, the middle cerebral artery occlusion (MCAO) mice model was used to evaluate the protective effect of Gs on stroke, and the administration of Gs significantly improved infarct volume, Bederson score, neurobiological function, apoptosis of neurons, and inflammation state in vivo. According to the data in vivo and the CM stimulated model in vitro, the beneficial effect of Gs came from the downregulation of the over-activity of microglia, such as the generation of inflammatory factors, dysfunction of mitochondria, production of ROS and so on. By RNA-seq analysis and Western-blot analysis, the JAK-STAT signal pathway plays a critical role in the anti-inflammatory effect of Gs. According to the results of molecular docking, inhibition assay, and thermal shift assay, the binding of Gs on JAK2 inhibited the activity of JAK2 which inhibited the over-activity of JAK2 and downregulated the phosphorylation of STAT3. Over-expression of a gain-of-function STAT3 mutation (K392R) abolished the beneficial effects of Gs. So, the downregulation of JAK2-STAT3 signaling pathway by Gs contributed to its anti-inflammatory effect on microglia in stroke. Our study revealed that Gs was benefit to stroke treatment by decreasing neuroinflammation in stroke as a potential drug candidate regulating the JAK2-STAT3 signal pathway.